Comparative Analysis on the Income of Rice Farmers Who Apply an Integration and Conventional System - Samsul Alam Fyka; Usman Rianse; Dewi Nurul Cahyani; Muhammad Aswar Limi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The integrated system of lowland rice and cattle farming is an agricultural approach that combines lowland rice farming with cattle farming in one integrated production system. This pattern provides the advantage of increasing income from lowland rice and cattle, whereas the conventional lowland rice pattern sources income only from lowland rice. This research aims to compare the income of farmers who implement an integrated lowland rice and cattle system with conventional lowland rice farmers. This research was conducted in the North Tongauna District, Konawe Regency, Southeast Sulawesi, Indonesia. The sample was determined using the Slovin technique, which was then continued using the proportional random sampling technique so that the number used was 43 farmers who implemented an integration system between lowland rice and cattle and 48 conventional lowland rice farmers in North Tongauna District, Konawe Regency. To answer the objective, use income analysis and the independent sample T-test. The results of the research show that there is a difference in income between farmers who implement an integrated system of lowland rice and cattle and conventional lowland rice farmers, namely farmers who implement an integrated system of lowland rice and cattle amounting to IDR41,047,139,-/ha/year. In contrast, for conventional lowland rice, The average income obtained was IDR 30,595,333/ha/year.